Era of gapless plant genomes: innovations in sequencing and mapping technologies revolutionize genomics and breeding. (February 2023) - Gladman, Nicholas; Goodwin, Sara; Chougule, Kapeel; Richard McCombie, William; Ware, Doreen
Abstract : Whole-genome sequencing and assembly have revolutionized plant genetics and molecular biology over the last two decades. However, significant shortcomings in first- and second-generation technology resulted in imperfect reference genomes: numerous and large gaps of low quality or undeterminable sequence in areas of highly repetitive DNA along with limited chromosomal phasing restricted the ability of researchers to characterize regulatory noncoding elements and genic regions that underwent recent duplication events. Recently, advances in long-read sequencing have resulted in the first gapless, telomere-to-telomere (T2T) assemblies of plant genomes. This leap forward has the potential to increase the speed and confidence of genomics and molecular experimentation while reducing costs for the research community. Graphical Abstract: ga1 Highlights: Sequencing technology has enabled gapless T2T plant genome assemblies. Gapless genomes are superior compared with nongapless constructions. Gapless genomes improve and hasten molecular breeding and gene characterization.